Poesia midiática de blogs locais: um diálogo com a poesia do Movimento Roraimeira sobre a questão da representação identitária do sujeito roraimense - Silva Filho, Antônio Hilário da (2014)
The current media technologies of networked communication have provided new forms of production, dissemination and storage of information, knowledge, art, bringing new and compelling impacts on the behavior and culture of modern man. In the 80s of the last century, began in Roraima the artistic-cultural movement known as Roraimeira, recognized today as the first great movement committed to clearly define the elements that constitute the cultural identity of Roraima people. With the advent of the internet, more precisely with the expansion of cybernetics and network communication, it is initiated in the first decade of this century an intense literary production of local writers in Roraima through a blog. Thus, this research is dedicated to the media literature study, specifically the poetic production produced and circulated in blogs by local authors in order to verify the contribution of this literature to the identity representation of the local subject, as well as analyzing how it articulates or dialogues with the identity representation present in the local literature of the artistic and cultural movement Roraimeira, which occurred before the cyber culture. Thus, the final product of this research pursued to answer the following problematic: Which identity elements that constitute the representation of the subject in the media poetry produced in Roraima and what is its relationship with the identity representation in Roraimeira movement considering the phenomenon of cyber culture and historical context multicultural Roraima ? Thus , the field of study for the analysis of media poetry was composed by three online blogs space, more precisely Pô & Cia (rmibielli.blogspot.com.br) , of the author Roberto Mibielli; Sobre Silêncio e Outras Coisas (isabella-coutinho.blogspot.com.br), of the author Isabella Coutinho and Eli Macuxi, Poesia Pura (elimacuxi.blogspot.com.br), of the author Eli Macuxi. In the search for answers to the questioning of the problem, we chose to use as methodology the bibliographical research and literary analysis of qualitative nature. The survey results showed that there is a large offset between the process of identity construction and representation of Roraimeira poetry and the media poetry of the analyzed blogs. While the poetry of Roraimeira is clearly focused on the identity construction of the local subject roraimense, the media poetry blogs of local writers is more directly affiliated to the processes of identity construction of the universal contemporary subject in an individualistic perspective and of fragmentation.